CALCULATING THE HEAT TRANSFER COEFFICIENT OF UNSTEADY HOMOGENEOUS OIL-GAS FLOW - M. SALIH, TAWFEEQ WASMI (Journal of Duhok University, 2017)
It is important to compute the heat transfer coefficient in a phase-change flow and enhance the empirical correlations to approximate the performance in many applications. In this work, the heat transfer coefficient of homogeneous two-phase flow with unsteady-state in vertical tube has been studied. The model that used to predict the flow pattern and the heat transfer coefficient for various flow velocities is determined theoretically. Some empirical relations are enrolled in order to find the fluid properties. The results are compared with that obtained experimentally and show responsible values. It is observed that the variation of heat transfer coefficient have been more oscillated and complicated as the flow velocity is increasing. This behavior could not be observed if the flow assumed as single flow, especially when the fluid seems to be gas. However, the theoretical value of void fraction has an average percentage difference ranges between (10-22) % to that obtained experimentally. While, the theoretical value of heat transfer coefficient has an average percentage difference ranges between (10-15) % to that obtained experimentally.